DOI: 10.31274/rtd-180817-5012
|View full text |Cite
|
Sign up to set email alerts
|

The association of performance ratings of teachers and achievement of students in the classroom

Abstract: This manuscript has been reproduced from the microfilm master. UMI fihns the text directfy fixmi the oiigiiiai or copy submitted. Thus, some thesis and dissertation copies are in typewriter fice, while others may be from any type of computer printer.The quality of this reproduction is dependent upon the quality of the copy submitted. Broken or indistinct print, colored or poor quality illustrations and photographs, print bleedthrough, substandard margins, and improper alignment can adversely affisct reproducti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(15 citation statements)
references
References 12 publications
0
15
0
Order By: Relevance
“…3. The findings of previous research conducted by Hidlebaugh (1973), Judkins (1987), Omotani (1993), Weber (1993), Wilcox (1995), Dietz (1996), and Wilkerson (1997),…”
Section: Delimitations Of the Smdymentioning
confidence: 51%
See 4 more Smart Citations
“…3. The findings of previous research conducted by Hidlebaugh (1973), Judkins (1987), Omotani (1993), Weber (1993), Wilcox (1995), Dietz (1996), and Wilkerson (1997),…”
Section: Delimitations Of the Smdymentioning
confidence: 51%
“…In a recent smdy by Wilkerson (1997), a significant positive correlation was foxmd to exist between smdents' ratings of their teacher and student achievement in three subjects. He also found that there was no correlation between how the principals rated the teachers with how well smdents performed.…”
mentioning
confidence: 86%
See 3 more Smart Citations